Metagenomic Analysis of Bacterial Communities of Antarctic Surface Snow - Lopatina, Anna; Medvedeva, Sofia; Shmakov, Sergey; Logacheva, Maria D.; Krylenkov, Vjacheslav; Severinov, Konstantin (Frontiers in Microbiology, 2016)
The diversity of bacteria present in surface snow around four Russian stations in Eastern Antarctica was studied by high throughput sequencing of amplified 16S rRNA gene fragments and shotgun metagenomic sequencing. Considerable class- and genus-level variation between the samples was revealed indicating a presence of inter-site diversity of bacteria in Antarctic snow. Flavobacterium was a major genus in one sampling site and was also detected in other sites. The diversity of flavobacterial type II-C CRISPR spacers in the samples was investigated by metagenome sequencing. Thousands of unique spacers were revealed with less than 35% overlap between the sampling sites, indicating an enormous natural variety of flavobacterial CRISPR spacers and, by extension, high level of adaptive activity of the corresponding CRISPR-Cas system. None of the spacers matched known spacers of flavobacterial isolates from the Northern hemisphere. Moreover, the percentage of spacers with matches with Antarctic metagenomic sequences obtained in this work was significantly higher than with sequences from much larger publically available environmental metagenomic database. The results indicate that despite the overall very high level of diversity, Antarctic Flavobacteria comprise a separate pool that experiences pressures from mobile genetic elements different from those present in other parts of the world. The results also establish analysis of metagenomic CRISPR spacer content as a powerful tool to study bacterial populations diversity.